EFEK KONSENTRASI ZAT PENGEMBAN TERHADAP KETUAAN WARNA PADA PENCELUPAN SERAT POLIESTER DENGAN ZAT WARNA DISPERSI - Agus Taufiq (Teknoin, 2006)
This Research study how far the  concentration of carrier agent  influence to the dyeing result of  of poliester cloth  with dyestuff of Resolin Red FB.          Dyeing process conducted with Resolin Red FB 200% as a dyestuff and four kinds of carrier agent  that is metilnaftalena, difenil, triklorbenzena and ortofenilfenol with concentration of carrier  agent, from  2 g / l, 4 g / l, 6 g / l and 8 g / l. Hereinafter conducted by examination of colour leveling to the result of dyeing process.        The result show that concentration of carrier agent give an effect  to the leveling of colour,  that is consentration excelsior yielded the better of colour leveling. This research also get, that  triklorbenzena type  yield the older colour from orto fenilfenol, metilnaftalena and difenil type, with the optimum concentration reached by 6 g / l.Keyword : dispersion, polyester,carrier agent, levelling of colour